Enhancing Learning Outcomes and Motivation: The Benefits of Related Humor Over Self-Disparaging Humor in Primary Chinese Education - Zhou, Weichen; Lee, Jun Choi (Sciedu Press, 2024)
Chinese language instruction is a valued primary education component, and educators have consistently sought methods to enhance teaching efficacy. While research has documented the numerous benefits of humor in the classroom, its application in primary school Chinese language education remains relatively unexplored. This study examined the comparative effectiveness of two humor approaches—related humor and self-disparaging humor—employed by teachers in primary school Chinese classes. A within-subjects design was adopted, with 45 primary school students participating in two Chinese lessons taught by the same instructor using different humor styles. Learning outcomes (measured by test scores) and motivation (assessed through self-reported questionnaires) were evaluated following each lesson. Additionally, informal semi-structured interviews were conducted upon completion of both lessons. Results indicated that related humor outperformed self-disparaging humor in terms of learning outcomes, student motivation, and overall student perception. These findings suggest that the strategic integration of related humor holds significant potential for enhancing teaching effectiveness in primary Chinese education. Future research should delve deeper into the specific advantages and limitations of humor in this context.